Review on Polyester Mooring Lines of Offshore Structures - Nur Aireen bt. Amran; J. Koto; C. L. Siow (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
Mooring line have several types of material which is chain, wire and synthetic fiber rope. Mostly, in oil and gas industry is use chain and wire rope as a mooring line for shallow water platform. When exploitation of oil and gas become deep, synthetic fiber is use as an alternative for mooring line. This paper focused on types of material and experimental by previous researcher for deep water mooring line. Beside that, the tensile test have been done for preliminary design stage. The test is to identify the material properties of mooring line. At this stage only focus on the steel wire rope with length 200mm and nominal diameter 2mm, 2.5mm, 6mm and 8mm. Finally, the conclusion and important summaries were presented according to the data collected.